Petrography 분석을 통한 고휘발 역청탄의 연소율 예측 - 이지환(Ji-Hwan Lee); 이대균(Dae-Gyun Lee); 야누아르 유디 이스워로(Yanuar Yudhi Isworo); 전충환(Chung-Hwan Jeon) (한국연소학회지, 2021)
The purpose of this study is to predict the combustion rate of high-volatile bituminous coal which is one of the important factors in determining the combustion conditions of a power plant. A method of predicting the combustion rate was proposed by integrating the petrography analysis elements related to the combustion rate. Since inertinite had a major effect on the combustion rate, it was possible to predict the combustion rate basically through the inertinite fraction, and petrofactor A was proposed by considering the Vitrinite reflectance value, and more accurate prediction was possible. Petrofactors B and C were proposed by additionally considering the standard deviation of vitrinite reflectance and the effect of liptinite to petrofactor A. The combustion rate could be more accurately predicted. Finally, petrofactor D was proposed considering all the previous factors, and the combustion rate was most accurately predicted. KCI Citation Count: 0